Geometrijske faze v kvantni mehaniki - Ulčakar, Lara (Matrika, 2015)
In the article geomeric phases, which occur when transforming quantum systems, are presented. First a classical version of geometric phase is described and later the Berry phase, which is explained on an example. Aharonov-Anandan phase is introduced. And the end the measurement of phase in described and possible application in quantum computing.
Keywords: Aharonov-Anandan phase; Aharonov-Anandanova faza; Berry phase; Berryjeva faza; geometric phases; geometrijske faze; kvantna mehanika; quantum mechanics